2021
DOI: 10.1093/ofid/ofab029
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Infection Does Not Change Disease Course or Inflammatory Pattern of SARS-CoV-2-Infected Patients Presenting at a Large Urban Medical Center in New York City

Abstract: Background The clinical impact of coronavirus disease 2019 (COVID-19) amongst people with HIV (PWH) remains unclear. In this retrospective cohort study of COVID-19, we compared clinical outcomes and laboratory parameters among PWH and controls. Methods 68 PWH diagnosed with COVID-19 were matched 1:4 to patients without known HIV diagnosis, drawn from a study population of all patients who were diagnosed with COVID-19 at an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…On the other hand, an immuno-depressed terrain may also create room for more severe clinical manifestations if infected with the novel coronavirus. Most of the previously available data did not provide evidence that persons living with HIV (PLWH) have a higher COVID-19 infection rate or a different disease course compared to those without HIV infection [ 4 , 5 , 6 ]. However, more recent studies suggest that COVID-19 infection in PLWH is associated with increased mortality and severe clinical outcomes particularly for those with CD4 counts below 200 cells/mm³ [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an immuno-depressed terrain may also create room for more severe clinical manifestations if infected with the novel coronavirus. Most of the previously available data did not provide evidence that persons living with HIV (PLWH) have a higher COVID-19 infection rate or a different disease course compared to those without HIV infection [ 4 , 5 , 6 ]. However, more recent studies suggest that COVID-19 infection in PLWH is associated with increased mortality and severe clinical outcomes particularly for those with CD4 counts below 200 cells/mm³ [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, most did not fully account for differences in comorbidities that likely impact the risk of COVID-19 outcomes [27,28]. When examining COVID-19 outcomes among patients diagnosed with COVID-19, several studies found that PWH have an increased risk of hospitalization but not hospital mortality despite matching for key cofounders including comorbidity burden [6,29]. There are several threats to the validity of conclusions from observational studies of the independent effect of HIV infection on risk for SARS-CoV-2 infection and its hospital-related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Children with MIS-C have grossly elevated inflammatory markers, proBNP, troponin and d-dimer [133]. People living with HIV with suppressed viral loads who are hospitalized with COVID-19 have similar levels of CRP, IL-6, ferritin and neutrophil counts as HIV-negative individuals, though these laboratory values were lower in people living with HIV without suppressed viral loads [134,135]. Chronic hepatitis B in COVID-19 inpatients may predispose to abnormal liver transaminases, and chronic active hepatitis C may be associated with COVID-19 severity [136,137].…”
Section: Discussionmentioning
confidence: 99%